Współczesne formy akomodacji misyjnej na przykładzie Kuby - Wiński, Adam (Annales Missiologici Posnanienses, 2023)
The presented article takes up the issue of missionary accommodation on the example of the Church in Cuba. It is shown in both theoretical (theology, conciliar teaching, papal teaching with special reference to Pope Francis) and practical (consultation with missionaries and the author’s own experience) assumptions. The purpose of the article is to reflect pastorally on the involvement of missionaries in pastoral ministry and to identify the essential accommodative ways used by them. The final conclusions point to the need for missionaries to be creative and open-minded in their search for new ways to evangelize, and to overcome obstacles in the way of proclaiming the Good News.